1999
DOI: 10.1083/jcb.147.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Rab6 Coordinates a Novel Golgi to ER Retrograde Transport Pathway in Live Cells

Abstract: We visualized a fluorescent-protein (FP) fusion to Rab6, a Golgi-associated GTPase, in conjunction with fluorescent secretory pathway markers. FP-Rab6 defined highly dynamic transport carriers (TCs) translocating from the Golgi to the cell periphery. FP-Rab6 TCs specifically accumulated a retrograde cargo, the wild-type Shiga toxin B-fragment (STB), during STB transport from the Golgi to the endoplasmic reticulum (ER). FP-Rab6 TCs associated intimately with the ER, and STB entered the ER via specialized periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
348
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(373 citation statements)
references
References 76 publications
(121 reference statements)
23
348
2
Order By: Relevance
“…1C). These data are consistent with the localization and function of Rab2 and Rab6 GTPases in modulating protein transport [36][37][38][39][40][41][42][43], suggesting that the GFP and FLAG epitop tagging did not influence the subcellular localization of Rab2 and Rab6 GTPases.…”
Section: Regulation Of the Cell-surface Expression Of α 2b -Ar And β supporting
confidence: 84%
See 3 more Smart Citations
“…1C). These data are consistent with the localization and function of Rab2 and Rab6 GTPases in modulating protein transport [36][37][38][39][40][41][42][43], suggesting that the GFP and FLAG epitop tagging did not influence the subcellular localization of Rab2 and Rab6 GTPases.…”
Section: Regulation Of the Cell-surface Expression Of α 2b -Ar And β supporting
confidence: 84%
“…Whereas Rab1 GTPase mediates anterograde transport of newly synthesized proteins from the ER to the Golgi, Rab2 and Rab6 GTPases modulate retrograde Golgi-to-ER transport, which is essential for retrieval of ER or Golgi resident proteins to maintain the organelle homeostasis as well as recycling of the components of the transport machinery required for anterograde transport [36][37][38][39][40][41][42][43]. We recently demonstrated that Rab1 GTPase differentially regulates the cell-surface targeting of distinct GPCRs [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, phospholipid composition in the surrounding membrane and interaction of Gb3-bound toxin with surface proteins are probably involved in the location of ST into membrane microdomains and subsequent sorting of endocytosis trafficking (Arab and Lingwood, 1996;Arab et al, 1998;Shimizu et al, 2003). Then, ST retrograde transport from the Golgi to ER uses a COP-Iindependent and Rab6-dependent pathway, the signalling molecules of which remain to be defined White et al, 1999). Interestingly, ricin, a plant toxin related to ST, which binds to glycosphingolipids and glycoproteins containing a terminal galactose, uses a cholesterol-dependent and glycosphingolipid-independent retrograde transport.…”
Section: Intracellular Trafficking Of St and Related Toxinsmentioning
confidence: 99%